Tantalum-doped titanium oxide film based on atomic layer deposition technology and preparation method and application thereof

The preparation of tantalum doped titanium oxide thin film as an electron selective contact layer through atomic layer deposition technology solves the problems of complex and high cost of silicon-based solar cells, and achieves efficient improvement of carrier selectivity and conversion efficiency.

CN116779719BActive Publication Date: 2025-04-11JIANGSU OCEAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310740974.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-04-11
Estimated Expiration
2043-06-21

AI Technical Summary

Technical Problem

The existing silicon-based solar cells have complex processes and high costs, resulting in limited improvement in conversion efficiency, especially in the preparation of carrier selective contact layers, such as parasitic absorption and Auger recombination.

Method used

Atomic layer deposition technology (ALD) was used to prepare tantalum doped titanium oxide (TaOx) films as electron selective contact layers, reducing preparation costs through low-temperature processes and improving the passivation and conductivity of the films.

Benefits of technology

It achieves efficient carrier selectivity, reduces parasitic absorption and Auger recombination, improves the conversion efficiency of solar cells, and reaches a championship efficiency of 21.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004297282210000011
    Figure HDA0004297282210000011
  • Figure HDA0004297282210000012
    Figure HDA0004297282210000012
  • Figure HDA0004297282210000021
    Figure HDA0004297282210000021
Patent Text Reader

Abstract

The present invention discloses a tantalum-doped titanium oxide film based on atomic layer deposition technology and a preparation method and application thereof. x (TTO) film is used as a passivation contact layer on the back of c-Si containing an oxide layer (natural oxidation) to achieve high photoelectric conversion efficiency. The present invention uses low-temperature ALD deposition technology to prepare TTO film to achieve good passivation effect (minority carrier lifetime τ eff =355.31μs) and conductivity (contact resistivity ρ c =0.7mΩ·cm 2 ), thereby achieving excellent carrier selectivity. The present invention applies tantalum-doped titanium oxide film to the back of N-type TOPCon battery as an electron selective contact layer, which can reduce parasitic absorption and Auger recombination compared with the traditional carrier selective contact layer. The prepared battery is air annealed at 130°C for 15 minutes to obtain the battery's champion efficiency of 21.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a tantalum-doped titanium oxide film based on atomic layer deposition technology and a preparation method and application thereof, belonging to the field of new energy. Background Art

[0002] How to use low-cost materials and simple and easy processes to achieve the preparation of high-efficiency solar cells has always been the ultimate goal of the continuous development of silicon-based solar cells. In 1941, Bell Laboratories first elaborated the concept of silicon-based photovoltaic devices, and in 1954, the first modern solar cell was developed using crystalline silicon (c-Si) as the substrate. Today, due to the increasingly serious energy crisis and the strong support of relevant national policies, solar photovoltaics have ushered in new challenges and opportunities. However, due to its complex process and expensive costs, it has become the biggest obstacle to its development. In order to reduce its cost and improve its efficiency, the most critical and basic method is to reduce its cost. Low-cost undoped carrier selective contact (also known as passivation contact) has become a hot topic for researchers due to its excellent passivation and conductive properties. Carrier selective contact is to deposit materials with wide bandgap and high or low work function on the c-Si surface to induce band bending. Its core is to use the asymmetry of conductivity to transmit one carrier (such as electrons) and hinder another carrier (such as holes). The carrier selective materials commonly used in the current production line include a-Si:H and Poly-Si, and the preparation methods mainly adopt PECVD and high-temperature annealing and other processes. When used as a passivation contact layer on the battery, it has high requirements on film quality and complex process. It involves high-temperature process and has large parasitic absorption and Auger recombination problems, which affects the improvement of conversion efficiency.

[0003] Existing technology - that is, the technical solution of the traditional carrier selective contact layer: using crystalline silicon as the substrate, using thermal oxidation to prepare silicon oxide (about 900°C) and plasma chemical vapor deposition (PECVD) to prepare polycrystalline or amorphous silicon (Poly-Si or a-Si:H) and other thin films as the carrier selective contact layer. The high temperature process of thermal oxidation is dangerous and has high requirements for equipment and instruments; when using PECVD to prepare microcrystalline or amorphous mixed Si thin films, it involves a high temperature process and complex process, there is a large parasitic absorption and Auger recombination, laser windowing is required, and the entire process has high production costs. Summary of the invention

[0004] Purpose of the invention: The first purpose of the present invention is to provide a tantalum-doped titanium oxide film based on atomic layer deposition technology. The second purpose of the present invention is to provide a method for preparing the tantalum-doped titanium oxide film. The third purpose of the present invention is to provide an application of the tantalum-doped titanium oxide film in the preparation of TOPCon batteries.

[0005] Technical solution: A method for preparing a tantalum-doped titanium oxide film based on atomic layer deposition technology of the present invention comprises the following steps:

[0006] (1) Chemically polishing and RCA cleaning the silicon wafer;

[0007] (2) The treated silicon wafer is placed in an ALD chamber, the chamber is kept in a vacuum state and at a constant temperature, tetrakis(dimethylamino)titanium is introduced into the chamber for purging, and then H2O (deionized water) is introduced for continued purging to obtain a TiO grown thereon. x Thin-film silicon wafers;

[0008] (3) (tert-butylamino) tris(ethylmethylamino)tantalum is introduced into the chamber for purging, and then H2O (deionized water) is introduced for continued purging to obtain a layer of TaO x Tantalum-doped titanium oxide thin films;

[0009] (4) Repeat steps (2) and (3) to obtain a multilayer TaO x Tantalum-doped titanium oxide thin film.

[0010] Furthermore, in step (1), chemical polishing and RCA cleaning of the silicon wafer comprises the following steps:

[0011] The silicon wafer is chemically polished with a NaOH solution, subjected to standard RCA cleaning and front texturing, and the oxide layer formed on the back of the silicon wafer during the RCA cleaning process is removed with an HF solution. The silicon wafer is left overnight to generate a silicon wafer with a natural oxide layer.

[0012] Furthermore, the concentration of the NaOH solution is 20%, and the concentration of the HF solution is 2%.

[0013] Furthermore, the silicon wafer is 182*182mm 2 (pseudo-square), solar-grade Cz silicon wafers with a thickness of 165μm and a resistivity of 0.5-3.5Ωcm.

[0014] Furthermore, in step (2), the constant temperature is 150°C. When tetrakis(dimethylamino)titanium is introduced into the chamber, the source bottle of tetrakis(dimethylamino)titanium is kept at a constant temperature of 85°C, the valve is closed after opening for 80-200ms, and the mixture is purged for 25-40s; when H2O (deionized water) is introduced, the source bottle of H2O is kept at a constant temperature of 35°C, the valve is closed after opening for 7-12ms, and the mixture is purged for 25-40s.

[0015] Furthermore, in step (3), when (tert-butylamino)tris(ethylmethylamino)tantalum is introduced into the chamber, the source bottle of (tert-butylamino)tris(ethylmethylamino)tantalum is kept at a constant temperature of 110°C, the valve is closed after opening for 150-250ms, and the chamber is purged for 25-40s; when H2O (deionized water) is introduced, the source bottle of H2O is kept at a constant temperature of 35°C, the valve is closed after opening for 7-12ms, and the chamber is purged for 25-40s.

[0016] Further, in step (4), step (2) is repeated for 20 cycles, and then step (3) is followed to prepare a film containing one layer of TaO x The Ta-doped TiO2 film is then formed, and step (2) is repeated for 20 cycles as one macrocycle. After 2 macrocycles, a film containing 2 layers of TaO x A tantalum-doped titanium oxide film is provided, wherein the tantalum-doped titanium oxide film is 3 nm thick, and a circulation ratio of Ta to Ti is 1:40.

[0017] The tantalum-doped titanium oxide film is prepared by the preparation method of the present invention.

[0018] The invention discloses an application of the tantalum-doped titanium oxide film in the preparation of TOPCon batteries.

[0019] Furthermore, the tantalum-doped titanium oxide film of the present invention is used as an electron selective contact layer on the back side of the TOPCon battery.

[0020] Furthermore, when preparing TOPCon cells, the front side of the cell is prepared by boron diffusion. + Emission grade, PECVD-Al2O3 / SiN x As a passivation layer and anti-reflection layer, the tantalum-doped titanium oxide film of the present invention is used as an electron selective contact layer on the back of the battery by screen printing grid lines and electrodes, and then a LiF / Al stack is used as a back electrode by thermal evaporation.

[0021] Furthermore, when thermal evaporation is used, the 4nm LiF / 200nm Al stack is used as the back electrode, and the vacuum degree during evaporation must reach 7*E -4 the following.

[0022] The present invention adopts PECVD (plasma enhanced chemical vapor deposition)-Al2O3 / SiN x The laminated dielectric film is deposited on the front of c-Si as a passivation layer and anti-reflection layer. The front electrode is prepared by screen printing technology, and then Ta-doped TiO is deposited by atomic layer deposition (ALD). x The (TTO) thin film is used as a passivation contact layer on the back of c-Si containing an oxide layer (natural oxidation), and LiF / Al stacking is prepared by thermal evaporation to achieve high photoelectric conversion efficiency.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0024] (1) The present invention uses low-temperature ALD deposition technology to prepare tantalum-doped titanium oxide thin film (TTO thin film) to achieve good passivation effect (minority carrier lifetime τ eff =355.31μs) and conductivity (contact resistivity ρ c =0.7mΩ·cm 2 ), thereby achieving excellent carrier selectivity.

[0025] (2) The present invention applies tantalum-doped titanium oxide film to the back of N-type TOPCon battery as an electron selective contact layer, which can reduce parasitic absorption and Auger recombination compared with the traditional carrier selective contact layer. The prepared battery is air annealed at 130°C for 15 minutes to obtain the battery's champion efficiency of 21.5%, open circuit voltage of 641.92mV, and short circuit current density of 39.27mA / cm 2 , filling factor 85.26%. Obviously better than pure TiO x or TaO x The film acts as an electron-selective contact layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 High-resolution transmission electron microscope (HR-TEM) image, EDX element scanning diagram and element line scanning diagram of the back side of the N-type TOPCon battery prepared in Example 1;

[0027] Figure 2 The overall structure diagram of the N-type TOPCon battery prepared in Example 1;

[0028] Figure 3 The TTO film in Example 1 and the TiO x Film and TaO in Comparative Example 3 x JV curve of the thin film prepared TOPCon cell after annealing at 130℃ for 15min;

[0029] Figure 4 The TTO film in Example 1 and the TiO x Film and TaO in Comparative Example 3 x EQE curve of thin film prepared TOPCon cell after annealing at 130℃ for 15min. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0031] Example 1

[0032] Cut with N type (100), 182*182mm 2 Size (pseudo-square), solar-grade Cz silicon wafer, silicon wafer thickness 165μm, resistivity 0.5-3.5Ωcm.

[0033] (1) The silicon wafer is chemically polished with a 20% NaOH solution, and then subjected to standard RCA cleaning and front texturing. The oxide layer formed on the back of the silicon wafer during the RCA cleaning process is removed with a 2% HF solution, and then the silicon wafer is left overnight to generate a silicon wafer with a natural oxide layer;

[0034] (2) Place the treated silicon wafer in the ALD chamber, keep the chamber in a vacuum state and at a constant temperature of 150°C, open the quick valve of tetrakis(dimethylamino)titanium, introduce tetrakis(dimethylamino)titanium into the chamber, keep the source bottle at a constant temperature of 85°C, close the quick valve after opening the valve for 80-200ms, and purge for 30s; then open the quick valve of H2O (deionized water), keep the source bottle at a constant temperature of 35°C, close the quick valve after opening the valve for 8ms, and purge for 30s to obtain the grown TiO x Thin-film silicon wafers;

[0035] (3) Open the quick valve of (tert-butylamino) tris(ethylmethylamino) tantalum, and introduce (tert-butylamino) tris(ethylmethylamino) tantalum into the chamber. Keep the source bottle at a constant temperature of 110°C. After opening the valve for 200ms, close the quick valve and purge for 30s. Then open the quick valve of H2O (deionized water), open the valve for 8ms, close the quick valve, and purge for 30s. At this time, the TiO x A TaO film is grown on the x The film is thus prepared to contain 1 layer of TaO x Ta-doped TiO2 thin film.

[0036] (4) Repeat the above step (2) for 20 cycles, and then follow step (3) to prepare a layer of TaO x The Ta-doped TiO2 film is then formed, and step (2) is repeated for 20 cycles as one macrocycle. After 2 macrocycles, a film containing 2 layers of TaO x Tantalum-doped titanium oxide film (film thickness 3nm and Ta:Ti cycle ratio of 1:40) is denoted as TTO.

[0037] (5) Boron diffusion is used to prepare P on the front side of the battery + Emission level, then PECVD-Al2O3 / SiN x As a passivation layer and anti-reflection layer, the grid lines and electrodes are then screen-printed; on the back of the battery, the above-mentioned 2 layers of TaO x The tantalum-doped titanium oxide film is used as the electron selective contact layer, and the 4nm LiF / 200nm Al stack is used as the back electrode by thermal evaporation. The vacuum degree during evaporation must reach 7*E -4Hereinafter, an N-type TOPCon battery is obtained, which is denoted as TTO based n-TOPCon.

[0038] The back cross section of the N-type TOPCon battery was analyzed by TEM and EDX line scanning. The results are as follows: Figure 1 shown. Figure 1 The high-resolution transmission electron microscope (HR-TEM) image, EDX element scanning diagram and element line scanning diagram of the back side of the N-type TOPCon battery prepared in Example 1; wherein, (a) is the cross-sectional HR-TEM image of the back side of the N-type TOPCon battery prepared in Example 1; (b) is the HR-TEM image of the c-Si / SiOx / TTO / LiF / Al interface on the back side of the N-type TOPCon battery prepared in Example 1; (c) is the EDX element scanning diagram of the back side of the N-type TOPCon battery prepared in Example 1; (d) is the c-Si / SiOx / TTO / LiF / Al interface on the back side of the N-type TOPCon battery prepared in Example 1. x EDX line scan of / TTO / LiF / Al interface.

[0039] Figure 1 (a) High-resolution transmission electron microscopy (HR-TEM) image showing the Si / SiOx / TTO / LiF / Al interface of the device with the highest PCE at a scale of 50 nm. Figure 1 (b) High-resolution transmission electron microscopy (HR-TEM) image shows the Si / SiO x / TTO / LiF / Al interface photographed at 5nm scale. Figure 1 (a) and (b) show that the back contact layer is composed of 1.5 nm SiO x , 3nm TTO, 4nm LiF, 200nm Al and a 0.5nm Ta layer between lithium fluoride and Al. Interestingly, the 0.5nm Ta layer is not naturally deposited but naturally formed. The O element in the TTO film can diffuse into the later layer, causing the Ta element to diffuse to maintain the balance of positive and negative charges in the TTO film. In addition, the Ta diffusion layer, as a diffusion barrier, has a unique structure that can prevent the diffusion of the Al electrode.

[0040] Depend on Figure 1 (c) It can be seen that the EDX element scanning can further confirm the rear structure of the SiOx / TTO / LiF / Al layer between c-Si and Al, and it is found that TiO x There is well-distributed Ta in the film, and an ultra-thin Ta layer exists between LiF and Al.

[0041] Depend on Figure 1 (d) It can be seen that the line scan can further confirm the SiO between c-Si and Al.x / TTO / LiF / Al layer, and the TiO x There is well-distributed Ta in the film, and an ultra-thin Ta layer exists between LiF and Al.

[0042] The overall structure of N-type TOPCon battery is as follows Figure 2 As shown by Figure 2 It can be seen that the overall cross-sectional structure of the TTO film applied to the n-type TOPCon solar cell has a full-area SiO x / TTO / LiF / Al superposition.

[0043] The N-type TOPCon cell prepared in this embodiment was annealed at 130°C for 15 minutes. The results showed that the N-type TOPCon cell prepared in this embodiment obtained the champion conversion efficiency of 21.5%, open circuit voltage of 641.92mV, and short circuit current density of 39.27mA / cm after annealing at 130°C. 2 , filling factor 85.26%.

[0044] Example 2

[0045] The experimental process is the same as in Example 1, except that in step (4), the above steps (2) and (3) are combined into one macrocycle, and 40 macrocycles are deposited to obtain 40 layers of TaO x Tantalum-doped titanium oxide film (film thickness is 3 nm and the Ta:Ti cycle ratio is 1:1).

[0046] The N-type TOPCon cell prepared in this embodiment was annealed at 130°C for 15 minutes. The results showed that the N-type TOPCon cell prepared in this embodiment obtained a champion conversion efficiency of 20.51% after annealing at 130°C, an open circuit voltage of 633.83mV, and a short circuit current density of 39.34mA / cm 2 , fill factor 82.26%

[0047] Example 3

[0048] The experimental process is the same as in Example 1, except that in step (4), the above step (2) is repeated for 3 cycles, and then a layer of TaO is prepared according to step (3). x The Ta-doped TiO2 film is then formed, and step (2) is repeated for 3 cycles as one macrocycle. After 12 macrocycles, a film containing 12 layers of TaO x The tantalum-doped titanium oxide film (thickness of the film is 3 nm and the cycle ratio of Ta:Ti is 1:6) is used to prepare an N-type TOPCon battery.

[0049] The N-type TOPCon cell prepared in this embodiment was annealed at 130°C for 15 minutes. The results showed that the N-type TOPCon cell prepared in this embodiment obtained a champion conversion efficiency of 20.35% after annealing at 130°C, an open circuit voltage of 653.4mV, and a short circuit current density of 39.59mA / cm 2 , filling factor 78.71%.

[0050] Example 4

[0051] The experimental process is the same as in Example 1, except that in step (4), the above step (2) is repeated for 7 cycles, and then step (3) is followed to prepare a film containing 1 layer of TaO x The Ta-doped TiO2 film is then formed, and step (2) is repeated for 8 cycles as one macrocycle. After 5 macrocycles, a film containing 5 layers of TaO x Tantalum-doped titanium oxide film (film thickness 3nm and Ta:Ti cycle ratio of 1:15). The tantalum-doped titanium oxide film is used to prepare an N-type TOPCon battery. The N-type TOPCon battery prepared in this embodiment is annealed at 130°C for 15 minutes. The results show that the N-type TOPCon battery prepared in this embodiment obtains a champion conversion efficiency of 19.91% after annealing at 130°C, an open circuit voltage of 628.61mV, and a short circuit current density of 39.23mA / cm 2 , filling factor 75.6%.

[0052] Example 5

[0053] The experimental process is the same as that of Example 1, except that in step (2), the treated silicon wafer is placed in the ALD chamber, and the chamber is kept in a vacuum state and at a constant temperature of 140°C.

[0054] The N-type TOPCon cell prepared in this embodiment was annealed at 130°C for 15 minutes. The results showed that the N-type TOPCon cell prepared in this embodiment obtained a champion conversion efficiency of 19.76% after annealing at 130°C, an open circuit voltage of 630.55mV, and a short circuit current density of 38.27mA / cm 2 , filling factor 81.89%.

[0055] Example 6

[0056] The experimental process is the same as that of Example 1, except that in step (2), the treated silicon wafer is placed in the ALD chamber, and the chamber is kept in a vacuum state and at a constant temperature of 200° C. Under these conditions, an N-type TOPCon cell is prepared.

[0057] The N-type TOPCon cell prepared in this embodiment was annealed at 130°C for 15 minutes. The results showed that the N-type TOPCon cell prepared in this embodiment had a conversion efficiency of 19.81%, an open circuit voltage of 635.04mV, and a short circuit current density of 39.95mA / cm after annealing at 130°C. 2 , filling factor 78.09%.

[0058] Comparative Example 1

[0059] References Liu Y, Zhang L, Cheng H, et al. Electron-Selective Contacts ATO / LiF / Al-Based High-Performance N-Type Silicon Solar Cells[J] Advanced Materials Interfaces, 2022, 9(31): 2201512, Al-doped TiO prepared by atomic layer deposition technology x The film is used as the electron selective contact layer, with a doping ratio (Al:Ti) of 1:5 and a thickness of 6nm. The deposited film is annealed in air at 250℃ for 15min. Then a 1.5nm LiF / 200nm Al stack is deposited by thermal evaporation as the back electrode, and the vacuum degree during evaporation must reach 7*E -4 The prepared battery was air annealed at 250°C for 15 min and achieved a champion efficiency of 19.9%, an open circuit voltage of 638.1 mV, and a short circuit current density of 40.3 mA / cm 2 , fill factor 77.4%. The N-type TOPCon cell prepared in Example 1 was air annealed at 250°C for 15 min to obtain a champion efficiency of 20.36%, an open circuit voltage of 645.3 mV, and a short circuit current density of 38.33 mA / cm 2 , the filling factor is 82.31%. This shows that the battery prepared in Example 1 can more effectively improve the conversion efficiency of the battery, and the new TTO film-based high-efficiency carbon-silicon solar cell provides a new way to achieve non-doped electron selective contact.

[0060] Comparative Example 2 Pure TiO x Thin films as electron-selective contacts for batteries

[0061] The experimental process is the same as that of Example 1, except that step (3) is removed and step (2) is repeated for 80 cycles to obtain 3 nm TiO x The film is denoted as TiO x based n-TOPCon.

[0062] The battery prepared in this comparative example was annealed at 130°C for 15 minutes. The results showed that the battery prepared in this comparative example obtained a champion conversion efficiency of 19.64%, an open circuit voltage of 626.26mV, and a short circuit current density of 38.88mA / cm after annealing at 130°C. 2 , filling factor 80.66%.

[0063] Comparative Example 3 Pure TaO x Thin films as electron-selective contacts for batteries

[0064] The experimental process is the same as that of Example 1, except that step (2) is removed and step (3) is repeated for 80 cycles to obtain 3 nm TaO x The film is denoted as TaO x based n-TOPCon.

[0065] The battery prepared in this comparative example was annealed at 130°C for 15 minutes. The results showed that the conversion efficiency of the battery prepared in this comparative example after annealing at 130°C was 19.57%, the open circuit voltage was 627.29mV, and the short circuit current density was 38.92mA / cm 2 , fill factor 80.17%. However, after annealing at 130℃, the efficiency of the battery dropped significantly to 17.55%, the open circuit voltage dropped to 589.66mV, and the short circuit current density dropped to 36.36mA / cm 2 , the filling factor dropped to 81.87%.

[0066] The N-type TOPCon battery prepared in Example 1 and the pure TiO x The cell with the film as the electron selective contact layer and the pure TaO prepared in Comparative Example 3 x The electrical and optical properties of the battery with the film as the electron selective contact layer were analyzed. Figure 3-4 shown. Figure 3 The TTO film in Example 1 and the TiO x Film and TaO in Comparative Example 3 x JV curves of TOPCon cells prepared with thin films respectively; Figure 4 The TTO film in Example 1 and the TiO x Film and TaO in Comparative Example 3 x EQE curves of TOPCon cells prepared by thin films. Figure 3 It can be seen that after applying the TTO film as an electron selective contact layer to the back of the TOPCon battery, its passivation performance is significantly improved, mainly reflected in the short-circuit current density and open-circuit voltage; its conductivity is also significantly improved, mainly reflected in the fill factor. Figure 4 It can be seen that when the TTO film is applied to the back of the TOPCon cell, its absorption of light in the long-wave band (800-1000nm) is significantly improved and higher than that of pure TaO x and pure TiO x Thin films as electron-selective contact layers for batteries.

[0067] The above experiments show that the present invention utilizes n-type c-Si / SiO x A new type of TOPCon solar cell was successfully fabricated in the / TTO / LiF / Al configuration, in which the TTO film served as an electron-selective passivation contact. The TTO film was optimized by a simple low-temperature ALD technique to provide an effective electron-selective contact. x Thin films and TaO x Compared with the ALD-TTO films, the best TTO films showed better surface passivation and conductivity. In addition, the ALD-TTO films also showed good thermal stability. Therefore, n-type solar cells based on TTO films are better than the known V oc ,I sc and FF are superior to the known TiO-based x Thin films and TaO x Finally, the present invention successfully achieved the highest PCE of n-type solar cells based on TTO thin films, which is 21.5%, much higher than that based on TaO x 19.57% of thin film solar cells and TiO x 19.64% of the film.

Claims

1. A method for preparing a tantalum-doped titanium oxide thin film based on atomic layer deposition technology, characterized in that: The following steps are involved: (1) Chemically polishing and RCA cleaning the silicon wafer: Chemically polish the silicon wafer with NaOH solution, perform standard RCA cleaning and front surface texturing, use HF solution to remove the oxide layer formed on the back of the silicon wafer during the RCA cleaning process, and leave the silicon wafer overnight to generate a silicon wafer with a natural oxide layer; (2) Place the treated silicon wafer into the ALD chamber, keep the chamber in a vacuum state and at a constant temperature, pass tetrakis(dimethylamino)titanium into the chamber for purging, and then pass deionized water for further purging to obtain a TiO2-grown silicon wafer. x The constant temperature is 150°C. When tetrakis(dimethylamino)titanium is introduced into the chamber, the source bottle of tetrakis(dimethylamino)titanium is kept at a constant temperature of 85°C, the valve is closed after opening for 80-200ms, and the valve is purged for 25-40 seconds; when deionized water is introduced, the source bottle of deionized water is kept at a constant temperature of 35°C, the valve is closed after opening for 7-12ms, and the valve is purged for 25-40 seconds; (3) (tert-butylamino) tris(ethylmethylamino)tantalum is introduced into the chamber for purging, and then deionized water is introduced for further purging to obtain a layer of TaO x When (tert-butylamino)tris(ethylmethylamino)tantalum is introduced into the chamber, the source bottle of (tert-butylamino)tris(ethylmethylamino)tantalum is kept at a constant temperature of 110°C, the valve is closed after opening for 150-250 ms, and purged for 25-40 s; when deionized water is introduced, the source bottle of deionized water is kept at a constant temperature of 35°C, the valve is closed after opening for 7-12 ms, and purged for 25-40 s; (4) Repeat step (2) for 20 cycles, and then follow step (3) to prepare a layer of TaO x The Ta-doped TiO2 film is then formed, and step (2) is repeated for 20 cycles as one large cycle. After 2 large cycles, a film containing 2 layers of TaO x A tantalum-doped titanium oxide film is provided, wherein the tantalum-doped titanium oxide film is 3 nm thick, and a circulation ratio of Ta to Ti is 1:

40.

2. The preparation method according to claim 1, characterized in that: The concentration of the NaOH solution is 20%, the concentration of the HF solution is 2%, and the silicon wafer is 182*182mm 2 , solar-grade Cz silicon wafers with a thickness of 165μm and a resistivity of 0.5-3.5 Ω·cm.

3. Tantalum-doped titanium oxide thin film obtained by the preparation method according to claim 1 or 2.

4. Use of the tantalum-doped titanium oxide film according to claim 3 in the preparation of TOPCon batteries.

5. The use according to claim 4, characterized in that: The tantalum-doped titanium oxide film described in claim 3 is used as an electron selective contact layer on the back side of the TOPCon battery.

6. The use according to claim 5, characterized in that: When preparing TOPCon cells, the front side of the cell is prepared by boron diffusion. + Emission grade, PECVD-Al2O3 / SiN x As a passivation layer and anti-reflection layer, the grid lines and electrodes are screen-printed, and the tantalum-doped titanium oxide film as claimed in claim 3 is used as an electron selective contact layer on the back of the battery, and then a LiF / Al stack is deposited by thermal evaporation as a back electrode.

Citation Information

Patent Citations

  • Aluminum-doped titanium oxide film based on atomic layer deposition technology and preparation method thereof

    CN113871493A

  • Methods for forming conductive titanium oxide thin films

    US20090297696A1

  • Tandem photovoltaic cell

    WO2023097365A1